Economic and environmental analysis of hydrogen production when complementing renewable energy generation with grid electricity. (15th December 2021) - Hurtubia, Byron; Sauma, Enzo
Abstract: Hydrogen (H 2 ) can be a critical factor in achieving a more sustainable society reducing carbon emissions worldwide in the long run. However, there are some challenges to be solved yet. One of these challenges is that, right now, the economical competitiveness of electrolysis production strongly depends on the Renewable Energy Sources (RES) availability. This paper analyzes the economic and environmental implications of complementing the power supply of a H 2 production plant that usually operates using only RES with grid electricity during the time RES are not available. For performing this analysis, we proposed an assessment model that incorporates Alkaline (ALK) and PEM electrolyzer technology features (such as the low dynamic load range of ALK electrolyzers, which is usually ignored when modeling H 2 production). Moreover, we introduce a new metric, named the LCOH&E, which captures the existing trade-off between reducing the Levelized Cost Of Hydrogen (LCOH) with more H 2 production using grid electricity and increasing CO 2 emissions by producing more H 2 with grid electricity. We illustrate the proposed assessment model with a case study based on real data from Chile. Our results show that the optimal fraction of grid electricity to be used in producing H 2 may be different when minimizing the LCOH and when minimizing the LCOH&E because of the LCOH-CO 2 emissions' trade off. Moreover, it is remarkable that using only 10% of grid electricity in an ALK electrolyzer, it is possible to increase the H 2 production in 25.7%, without significantly increasing the CO 2 emission level. Highlights: This paper analyzes the value of adding grid electricity to a pure RES H2 production plant. The Levelized Cost of Hydrogen and CO2 emissions are obtained for Alkaline and PEM electrolyzers. We combine the Levelized Cost of H2 and the CO2 emissions in a single cost function to optimize. The assessment model incorporates crucial ALK and PEM technology features of the H2 production. Using only 10% of grid electricity in an ALK electrolyzer, H2 production can increase 25.7%.